Pengaruh Pupuk Organik Gulma Siam (Chromolaena odorata L.) dan Ampas Bungkil Mimba (Azadiracta indica A.Juss) pada Sifat Kimia Tanah dan Performa Tanaman Padi Hitam - Rizky Fauzi; Octaviani .; Reynaldi Yunior; Vira Kusuma Dewi; Santika Sari; Sri Hartati; Dwi Harya Yudistira; Yongki Umam Sandi (Soilrens, 2018)
ABSTRACT A black rice cultivation study was conducted at Kampung Cinenggang, Cileles Villages, Jatinangor.  This research analyzed the effect of organic fertilizer such as siam weed compost and neem cake waste to black rice growth and soil chemicals. The experiment was arranged in randomized block design consisted of five treatments and six  replications as follow : neem cake waste , siam weed compost, cow manure, urea  were used as the N sources by comparing with no application (control). Overall the result of the study showed that there were no significant differences among treatment in plant growth characters such as plant height and SPAD, except control. In tiller number, the effect of neem cake waste and siam weed compost were significant different if compared with other treatments. Furthermore, the effect of neem cake waste gives a positive effects to soil chemicals which in turn enhanced the growth of black rice. it is recommended that organic fertilizers (neem cake waste and siam weed compost) be utilized instead of chemical fertilizer.  Keywords:  black rice , neem cake waste, organic fertilizer,  siam weed compost, plant growth, soil chemicals